Desain Material Sweeper Untuk Kendaraan Penghisab Debu Vulkanik - Wikan Sakarinto; Andhi Akhmad Ismail; Andi Pratama; Putri Chairany (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
In overseas, the road sweeper have been producted.  But, the expensive of import tax will befundamental problem for realisation the road sweeper from the overseas. The goal of this observationis making the the road sweeper which will be raised the amout in the future according UGM needed.And the part of  the road sweeper is the sweeper itself. The problem which has been observated isgiving the proper testing for steel wire as the based material in making a sweeper. Because of that,for knowing the proper testing in the steel wire, then doing observation which has given a differenttreatment. As the component which has the work with lots of friction, so the sweeper must have highhardness, high wear resistance, and high tensile strength. Based on the result of spectrometer analiticreport which was did in science and accelerator technology laboratory-  BATAN. Based on the resultpicture of micro sweeper structur observation with material stainless steel in litterature has asimilarity with the picture of austenite and ferrite micro structure which has several   overages,especially in strength and high resistance to intergranular corrosion.